Emphasizing the Role of Diplomatic Agents for Repatriation of Ex-Foreign Terrorist Fighters (FTF): Study of Indonesia - Triyana, Heribertus Jaka (Jambe Law Journal, 2024)
Repatriation of the ex-Foreign Terrorist Fighters (FTFs) has been initiated since 2020 where many ex-Indonesians are trapped and scammed in the conflicting areas. These individuals, often branded as ex-nationals upon leaving their homelands, have engaged in violent conflicts in Syria, Iraq, and beyond. With ISIS’s territorial grip weakening, these ex-FTFs now attempt to return to their origin countries, such as Indonesia. The analysis in this paper is mainly constructed by the role and function of diplomatic and consular agents on their repatriation. They are directed to the existence of customary international law as the primary source of international law in order to find out the relevance of their repatriation. It provides a legal framework of analysis on how the state conducts dealing with these complex emergencies abroad on state protection to its own nation abroad. The clarity and robust guidance could reduce complex dilemmas for the governments in managing this repatriation. While some call for imprisonment or even elimination, repatriation highlights the crucial role of reintegration and rehabilitation programs. It underscores the legal responsibilities of states under international law, advocating for the protection of human rights while maintaining national public safety conducted by diplomatic and consular agents